2011
DOI: 10.4084/mjhid.2011.054
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Prothrombin G20210a Mutation in the Mediterranean Region

Abstract: There are many genetic and acquired risk factors that are known to cause venous thromboembolic disorders (VTE). One of these is the Prothrombin G20210A mutation, which has been identified in 1996. Prothrombin G20210A mutation causes higher levels of the clotting factor prothrombin in the blood of carriers, which creates a higher tendency towards blood clotting (hypercoagulability), and therefore the carriers become at higher risk of developing VTE. High prevalence of Prothrombin G20210A mutation was reported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 98 publications
(13 reference statements)
3
39
0
2
Order By: Relevance
“…In contrast, prothrombin G20210A polymorphism was found very rare or even absent in asian and African populations (Jadaon 2011;Hessner et al 1999;Isshiki et al 1998;Wan Zaidah et al 2010;Angchaisuksiri et al 2000). It is suggested that this variant is restricted to Caucasian populations.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, prothrombin G20210A polymorphism was found very rare or even absent in asian and African populations (Jadaon 2011;Hessner et al 1999;Isshiki et al 1998;Wan Zaidah et al 2010;Angchaisuksiri et al 2000). It is suggested that this variant is restricted to Caucasian populations.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, FII 20210A mutation is met only in Caucasians with an average prevalence of 2-3% and increases the risk of venous thrombosis 3-fold [5]. The highest prevalence of FII 20210A is encountered in the Southern Europe, in the Mediterranean region and in the Middle East [10, 37]. …”
Section: Discussionmentioning
confidence: 99%
“…and in Lebanon ( p = 14.4% and 1.3–3.6%, resp.) [37, 38]. Assuming that the reports of Gül et al [8, 9] indicate that FVL and FII 20210A mutations are genetically associated with BD and act synergistically with the tenderness of BD for thrombotic events, one could say that this is one reason that explains why the prevalence of vascular BD is lower in Japan ( p = 6%) [32] and higher in Turkey ( p = 14.3–26%) [29, 30] and in Lebanon ( p = 36.8%) [39].…”
Section: Discussionmentioning
confidence: 99%
“…In these patients other factors, such as inherited thrombophilia, may play a significant role (3). In recent decades several hereditary coagulation abnormalities have been identified as additional risk factors for thrombotic events and the most frequently found genetic thrombophilic factors in the European Caucasian population were Factor V Leiden (FVL) (1-14% in the healthy population and 9-50% in VTE) and factor II -prothrombin G20210 A polymorphisms (0-5% in the healthy population and 3.2-17.2% in VTE) (4,5). Although the predominant clinical manifestation of inherited thrombophilia is venous thrombosis, its contribution to arterial thrombosis still remains debated (6).…”
Section: Thrombophilia Genetic Testing In Romanian Young Womenintrodumentioning
confidence: 99%